Innovative Pedagogical Technology in the Education and Training System: The Importance of Project Method Technology - Dustkabilovich, Rakhimov Oktyabr; Laylo Аshurova (European Journal of Life Safety and Stability (2660-9630), 2022)
In the following article, the importance of education and upbringing in higher education institutions in the development of the state and society, the classification of innovative pedagogical technologies and the significance of one of the innovative pedagogical technologies - project method technology, the methodology of its implementation in the class, the main thesis of this technology in the training of specialists and their social and professional role in the formation of competence is demonstrated.